2010
DOI: 10.1136/oem.2009.052571
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and bladder cancer in a population-based case–control study in Northern New England

Abstract: Objectives We used data from a large, population-based case-control study in New England to examine relationships between occupation, industry, and bladder cancer risk. Methods Lifetime occupational histories were obtained by personal interview from 1,158 patients newly diagnosed with urothelial carcinoma of the bladder between 2001 and 2004 among residents of Maine, New Hampshire, and Vermont, and from 1,402 population controls selected from Department of Motor Vehicle records (ages 30 to 64 years) or Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 58 publications
0
40
1
1
Order By: Relevance
“…Bladder cancer risk was highest for plumbers working prior to 1960. 58 In our analysis, plumbing was not statistically significant (95% CI, 0.85-2.38). The concentration of heavy metals in solder has decreased since the 1960s.…”
Section: Workers Exposed To Heavy Metalscontrasting
confidence: 56%
See 1 more Smart Citation
“…Bladder cancer risk was highest for plumbers working prior to 1960. 58 In our analysis, plumbing was not statistically significant (95% CI, 0.85-2.38). The concentration of heavy metals in solder has decreased since the 1960s.…”
Section: Workers Exposed To Heavy Metalscontrasting
confidence: 56%
“…58 Solder and welding fumes contain lead oxide, heavy metals (eg, arsenic, cadmium, chromium, and nickel) and colophony (rosin-based flux containing acetone and carbon monoxide). Bladder cancer risk was highest for plumbers working prior to 1960.…”
Section: Workers Exposed To Heavy Metalsmentioning
confidence: 99%
“…Findings of two cohort studies showed that the risk of BC increased in individuals exposed to 1-naphthylamine, 2-naphthylamine, benzidine, and 4-aminobiphenyl over a period of 60 years (Case and Hosker, 1954;Melick et al, 1955). Findings from a case-control study by Samniac et al showed that the risk of BC in men employed in the printing industry as machine operators (case group) was significantly higher than that for the control group (Colt et al, 2010). Also, Case et al found that the BC risk in British staff exposed to 2-naphthylamine was 200 times higher than other staff (Case and Hosker, 1954).…”
Section: -1 Aromatic Aminesmentioning
confidence: 99%
“…This is attributable to both the latency periods that often exceed 20 years [1][2][3], and the significant range of chemical agents associated with increased risk of bladder cancer [3][4][5][6][7]. Recent evidence suggests that metal workers, car mechanics, plumbers [8], those exposed to intermediates in rubber and plastics manufacture [9], and those working in occupations allied to agriculture or medicine and health [10] could be at risk of developing UC. With respect to aromatic amines, risk is highest in those exposed at a younger age, those with over 10 years of exposure [11] and amongst certain categories of painters [12].…”
Section: Introductionmentioning
confidence: 99%